Non-enzymatic Lysine Lactoylation of Glycolytic Enzymes. Issue 2 (20th February 2020) - Gaffney, Dominique O.; Jennings, Erin Q.; Anderson, Colin C.; Marentette, John O.; Shi, Taoda; Schou Oxvig, Anne-Mette; Streeter, Matthew D.; Johannsen, Mogens; Spiegel, David A.; Chapman, Eli; Roede, James R.; Galligan, James J.
Summary: Post-translational modifications (PTMs) regulate enzyme structure and function to expand the functional proteome. Many of these PTMs are derived from cellular metabolites and serve as feedback and feedforward mechanisms of regulation. We have identified a PTM that is derived from the glycolytic by-product, methylglyoxal. This reactive metabolite is rapidly conjugated to glutathione via glyoxalase 1, generating lactoylglutathione (LGSH). LGSH is hydrolyzed by glyoxalase 2 (GLO2), cycling glutathione and generating D-lactate. We have identified the non-enzymatic acyl transfer of the lactate moiety from LGSH to protein Lys residues, generating a "LactoylLys" modification on proteins. GLO2 knockout cells have elevated LGSH and a consequent marked increase in LactoylLys. Using an alkyne-tagged methylglyoxal analog, we show that these modifications are enriched on glycolytic enzymes and regulate glycolysis. Collectively, these data suggest a previously unexplored feedback mechanism that may serve to regulate glycolytic flux under hyperglycemic or Warburg-like conditions. Graphical Abstract: Highlights: Lysine lactoylation occurs via a non-enzymatic acyl transfer from lactoylglutathione Glycolytic enzymes are heavily modified by lactoylation Glyoxalase 2 is the critical regulator for lactoylglutathione and lysine lactoylation Glycolytic output is significantly repressed in glyoxalase 2 knockout cells Abstract : Gaffney et al. describe a lysine modification derived from a non-enzymatic acyl transfer from the secondary glycolytic intermediate, lactoylglutathione. This modification, lysine lactoylation, is enriched on primary glycolytic enzymes and regulates metabolic output.